The Power of the Poetic Lens: Why Teachers Need to Read Poems Together - Amy L Eva; Carrie A Bemis; Marie F Quist; Bill Hollands (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
Poetry reading circles can become the means for new (and experienced) teachers to reflect on their professional growth.